Postgraduate Students' English Learning Motivation in Practicing CEFR Preparation Level B1 Reading - Sukarton Sukarton; Abraham Adiel Yudha Pramudya; Rizdika Mardiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2025)
The Common European Framework of Reference for Languages (CEFR) is globally adopted as a standard framework for measuring language proficiency across various contexts, including English language education. Despite its increasing application, little is known about how CEFR-based test preparation impacts learner motivation, particularly among postgraduate students. This study aims to explore the motivation of postgraduate students to practice the CEFR preparation level B1 reading test. Using a qualitative narrative inquiry design, data were collected through questionnaires, observation sheets, and self-reflection reports and analyzed thematically to identify key motivational patterns. The results show that 90% of participants reported feeling motivated by the CEFR B1 reading practice, while 10% expressed a neutral stance. Seven prominent motivational terms emerged from the analysis, they are finished, positive, supported, whole, carefully, focused, and practiced. These findings suggest that structured CEFR preparation activities can enhance learners’ self-perception, focus, and persistence in English learning.